2015
DOI: 10.1021/jp510691e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Local Structure and Phase Behavior of Imidazolium-Based Protic Ionic Liquids

Abstract: We report on the effect of water on local structure and phase behavior of two protic ionic liquids, C2HImTFSI and C2HImTfO. Raman and infrared spectroscopy are employed to investigate the local coordination state. We find that water interacts weakly with TFSI(-) while more specifically with TfO(-) through the -SO3 group. Additionally, we observe that upon addition of water the -NH stretching frequency does not change in C2HImTFSI, while it red-shifts in C2HImTfO, indicative of different hydrogen bonding config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
70
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 56 publications
(142 reference statements)
13
70
3
Order By: Relevance
“…The wavenumber correlation was found in experimental data where the assignment was made to the vibrational mode νC(2)‐H of the Raman band at around 3080 cm −1 and to the vibrational mode νC(4,5)‐H of the Raman band at around 3150 cm −1 (Table ). LC phase formation and the strength of the cation–anion interaction through hydrogen bonding were investigated monitoring the wavenumber of Raman spectra bands assigned to the [C 10 mim] + cation C–H stretching vibrational modes of imidazolium ring at the carbon positions 2, 4, and 5 . According to the literature, the hydrogen bond involving aromatic C–H on the imidazolium ring classified as red shift H bond .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wavenumber correlation was found in experimental data where the assignment was made to the vibrational mode νC(2)‐H of the Raman band at around 3080 cm −1 and to the vibrational mode νC(4,5)‐H of the Raman band at around 3150 cm −1 (Table ). LC phase formation and the strength of the cation–anion interaction through hydrogen bonding were investigated monitoring the wavenumber of Raman spectra bands assigned to the [C 10 mim] + cation C–H stretching vibrational modes of imidazolium ring at the carbon positions 2, 4, and 5 . According to the literature, the hydrogen bond involving aromatic C–H on the imidazolium ring classified as red shift H bond .…”
Section: Resultsmentioning
confidence: 99%
“…LC phase formation and the strength of the cation-anion interaction through hydrogen bonding were investigated monitoring the wavenumber of Raman spectra bands assigned to the [C 10 mim] + cation C-H stretching vibrational modes of imidazolium ring at the carbon positions 2, 4, and 5. [29] According to the literature, the hydrogen bond involving aromatic C-H on the imidazolium ring classified as red shift H bond. [30,31] In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SI-4. A blue-shift of these vibrations is typically associated with the anion experiencing a stronger interaction [42], which may a priori be to the cation or the enzyme's surface. In any case, the observed shift is rather small (below 1 cm À1 ) indicating that the change in interaction strength is marginal.…”
Section: Ionic Liquid-enzyme Interactionsmentioning
confidence: 99%
“…Thus, our conclusion is that for both C 2 HImTfO and C 10 C 1 ImTFSI the ionic liquid-enzyme interaction is weak and such that the structure of the enzyme is not significantly altered. This is interesting since the protic ionic liquid C 2 HImTfO has a propensity to form hydrogen bonds, for instance with water, through both the cation and the anion [42]. Nonetheless, infrared difference spectra in the range of O-H stretching show that water hydrating the enzyme and water coordinated to C 2 HImTfO maintain their nature even in the C 2 HImTfO-impregnated enzyme.…”
Section: Ionic Liquid-enzyme Interactionsmentioning
confidence: 99%
“…Recent studies have shown that the presence of water or other organic solvents in ILs can have great effect on the physical and chemical properties of the ILs, such as viscosity, electrical conductivity, polarity, reactivity, and solvation properties. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Therefore, nowadays, as a simple strategy to expand the applications of those Coulomb fluids, the mixtures of ILs with other solvents have drawn growing attention in many industrial processes, such as synthesis, catalysis, industrial cleaning, solvent extraction, and separation. Then, in these applications, to find the suitable cosolvent partner of ILs, it is crucial to understand not only the properties of pure ILs, but also those of ILs-cosolvent mixtures.…”
Section: Introductionmentioning
confidence: 99%